Locating Development as a New ‘Discipline’ (Nepalese Journal of Development and Rural Studies, 2018)
Development is an essentially contested discourse and debated issue; both in theoretical and empirical world. With this proposition, this paper offers a synthesis of multifaceted dimensions of development. Methodologically the paper follows a critical perspective, though it is based only on secondary data and prepared as a synthesis paper drawing insights from various literatures. The major arguments of the paper include that: development is constantly becoming contradictory, involving different actors, agencies, and structures. The paper concludes with the remark that development is being questioned elsewhere, and its conclusion in terms of theory and practice is yet contradictory to have universal validation.